2021
DOI: 10.1016/j.cytogfr.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Is Toll-like receptor 4 involved in the severity of COVID-19 pathology in patients with cardiometabolic comorbidities?

Abstract: Highlights Some inflammatory diseases are related to severe forms of COVID-19, characterized by an immune system overactivation. SARS-CoV-2 Spike protein binds with human innate immune receptors, mainly TLR4, increasing secretion of IL‐ 6 and TNF‐ α. The main inflammatory diseases seen as risk factors for COVID-19 are hypertension, diabetes, obesity, and atherosclerosis. The TLR4 signaling pathway is connected to inflammatory diseases se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 149 publications
4
76
0
Order By: Relevance
“…However, they do mention that some TLR4 antagonists including Eritoran and TAK242 (both proposed here) were used successfully in the treatment of inflammation associated with cancer, rheumatoid arthritis, and other inflammatory diseases ([ 151 ] and references therein). Based on our proposal (see Disclosure: DOI) and Choudhury and Mukherjee [ 30 ], another recent report speculates on the hypothesis that the TLR4 signalling pathway provides opportunities for the targeting of TLR4 by antagonists in severe COVID-19 patients with cardiometabolic complications provided that the involvement of TLR4 is proven [ 152 ]. Based on the comprehensive and detailed evidence reviewed here, we support in principle the trial of TLR4 antagonists in the treatment of severe COVID-19 infections to (1) reduce the severe inflammation, particularly in the lungs and heart, but also systemically (2) block the entry mechanism involving ACE2 upregulation that we have proposed.…”
Section: Possible Therapeutic Options For Treating Covid-19 Whichmentioning
confidence: 99%
“…However, they do mention that some TLR4 antagonists including Eritoran and TAK242 (both proposed here) were used successfully in the treatment of inflammation associated with cancer, rheumatoid arthritis, and other inflammatory diseases ([ 151 ] and references therein). Based on our proposal (see Disclosure: DOI) and Choudhury and Mukherjee [ 30 ], another recent report speculates on the hypothesis that the TLR4 signalling pathway provides opportunities for the targeting of TLR4 by antagonists in severe COVID-19 patients with cardiometabolic complications provided that the involvement of TLR4 is proven [ 152 ]. Based on the comprehensive and detailed evidence reviewed here, we support in principle the trial of TLR4 antagonists in the treatment of severe COVID-19 infections to (1) reduce the severe inflammation, particularly in the lungs and heart, but also systemically (2) block the entry mechanism involving ACE2 upregulation that we have proposed.…”
Section: Possible Therapeutic Options For Treating Covid-19 Whichmentioning
confidence: 99%
“…SARS-CoV-2 mediated myocardial apoptosis, cardiogenic shock, myocardial ischemia and inflammatory injury were related to the down-regulation of ACE2 in the myocardium [ [51] , [52] ]. The spike protein of SARS-CoV-2 might bind to TLR4 to trigger transmembrane stimulation [ [53] , [54] ]. Then, TLR4 activated interferon (IFN)-regulatory factors (IRF3 and IRF7), leading to increased expression of one of the hub genes IFNB1 and further enhancive the secretion of IFN-β [ [55] , [56] ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there have been studies claiming an important role of TLR4 in SARS-CoV-2, as in silico studies identified TLR4 as very likely to respond to spike proteins of SARS-CoV-2 [ 49 ]. Interestingly, TLR4 is also associated with cardiometabolic comorbidities such as obesity and hypertension, which are known risk factors for severe COVID with hyperinflammation [ 50 ]. Furthermore, TLR4-deficient mice were less susceptible to acute respiratory distress syndrome (ARDS) upon inhalation trauma [ 51 ].…”
Section: Discussionmentioning
confidence: 99%